Mechanical sensitivity and electrophysiological properties of acutely dissociated dorsal root ganglion neurons of rats. (10th November 2016) - Viatchenko-Karpinski, Viacheslav; Gu, Jianguo G.
Highlights: Primary afferent fibers use mechanically activated (MA) currents to transduce innocuous and noxious mechanical stimuli. It is largely unknown about the differences in MA currents between the afferents for sensing innocuous and noxious stimuli. This study identified differences in MA currents between non-nociceptive-like and nociceptive-like DRG neurons. We also showed differences in electrophysiological properties between these two groups of mechanically sensitive neurons. Our findings provide insights into mechanisms of sensory encoding for innocuous and noxious mechanical stimuli. Abstract: Primary afferent fibers use mechanically activated (MA) currents to transduce innocuous and noxious mechanical stimuli. However, it is largely unknown about the differences in MA currents between the afferents for sensing innocuous and noxious stimuli. In the present study, we used dorsal root ganglion (DRG) neurons acutely dissociated from rats and studied their MA currents and also their intrinsic membrane properties. Recorded from small-sized DRG neurons, we found that most of these neurons were mechanically sensitive (MS) showing MA currents. The MS neurons could be classified into nociceptive-like mechanically sensitive (Noci-MS) and non-nociceptive-like mechanically sensitive (nonNoci-MS) neurons based on their action potential shapes. Noci-MS neurons responded to mechanical stimulation with three types of MA currents, rapidly adapting (RA), intermediately adapting (IA), and slowly adapting (SA) currents. In contrast, almost all nonNoci-MS neurons showed RA current type in response to mechanical stimulation. Mechanical thresholds had a broad range for both nonNoci-MS and Noci-MS neurons, and the thresholds were not significantly different between them. However, MA current densities were significantly smaller in Noci-MS than in nonNoci-MS neurons. Noci-MS and nonNoci-MS neurons also showed significant differences in their electrophysiological properties including action potential (AP) thresholds and AP firing patterns. These differences may contribute to the differential sensory encoding for innocuous and noxious mechanical stimuli.